Structural Analysis of Alterations in Zebrafish Muscle Differentiation Induced by Simvastatin and Their Recovery with Cholesterol. (June 2015) - Campos, Laise M.; Rios, Eduardo A.; Midlej, Victor; Atella, Georgia C.; Herculano-Houzel, Suzana; Benchimol, Marlene; Mermelstein, Claudia; Costa, Manoel Luís
In vitro studies show that cholesterol is essential to myogenesis. We have been using zebrafish to overcome the limitations of the in vitro approach and to study the sub-cellular structures and processes involved during myogenesis. We use simvastatin—a drug widely used to prevent high levels of cholesterol and cardiovascular disease—during zebrafish skeletal muscle formation. Simvastatin is an efficient inhibitor of cholesterol synthesis that has various myotoxic consequences. Here, we employed simvastatin concentrations that cause either mild or severe morphological disturbances to observe changes in the cytoskeleton (intermediate filaments and microfilaments), extracellular matrix and adhesion markers by confocal microscopy. With low-dose simvastatin treatment, laminin was almost normal, and alpha-actinin was reduced in the myofibrils. With high simvastatin doses, laminin and vinculin were reduced and appeared discontinuous along the septa, with almost no myofibrils, and small amounts of desmin accumulating close to the septa. We also analyzed sub-cellular alterations in the embryos by electron microscopy, and demonstrate changes in embryo and somite size, septa shape, and in myofibril structure. These effects could be reversed by the addition of exogenous cholesterol. These results contribute to the understanding of the mechanisms of action of simvastatin in muscle cells in particular, and in the study of myogenesis in general.